Utilization Of Instagram Social Media On The @Qowaidul_Lughoh Account As An Arabic Language Learning Media - dini, Putri Dini Fatimah; Nanda Pratama; Anggia Rita Andriana (IJAS: International Journal of Arabic Studies, 2025)
This study aims to describe the use of Instagram social media on the @qowaidul_lughoh account as a medium for learning Arabic. The background of the study is based on the development of information and communication technology that drives transformation in the world of education, especially in learning Arabic. Instagram as one of the popular social media platforms among the younger generation, offers various features that can be used to improve the effectiveness and learning of learning. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation of the manager and followers of the @qowaidul_lughoh account. The results of the study indicate that the use of Instagram through the @qowaidul_lughoh account is able to provide varied, interactive, and easily accessible Arabic learning materials anytime and anywhere. Features such as posting images, videos, stories, and reels are used to present understanding, grammar, and exercises that support mastery of the four basic Arabic skills (istima', kalam, qira'ah, and kitabah). In addition, the interaction between managers and followers through the comments column and direct messages increases motivation and active participation in learning. This study concludes that Instagram social media, especially through educational accounts such as @qowaidul_lughoh, can be an alternative media for learning Arabic that is effective, innovative, and adaptive to the needs of learners in the digital era.